MoSnt2-dependent deacetylation of histone H3 mediates MoTor-dependent autophagy and plant infection by the rice blast fungus Magnaporthe oryzae. Issue 9 (2nd September 2018) - He, Min; Xu, Youpin; Chen, Jinhua; Luo, Yuan; Lv, Yang; Su, Jia; Kershaw, Michael J.; Li, Weitao; Wang, Jing; Yin, Junjie; Zhu, Xiaobo; Liu, Xiaohong; et al.
ABSTRACT: Autophagy is essential for appressorium-mediated plant infection by Magnaporthe oryzae, the causal agent of rice blast disease and a major threat to global food security. The regulatory mechanism of pathogenicity-associated autophagy, however, remains largely unknown. Here, we report the identification and functional characterization of a plausible ortholog of yeast SNT2 in M. oryzae, which we term MoSNT2 . Deletion mutants of MoSNT2 are compromised in autophagy homeostasis and display severe defects in autophagy-dependent fungal cell death and pathogenicity. These mutants are also impaired in infection structure development, conidiation, oxidative stress tolerance and cell wall integrity. MoSnt2 recognizes histone H3 acetylation through its PHD1 domain and thereby recruits the histone deacetylase complex, resulting in deacetylation of H3. MoSnt2 binds to promoters of autophagy genes MoATG6, 15, 16, and 22 to regulate their expression. In addition, MoTor controls MoSNT2 expression to regulate MoTor signaling which leads to autophagy and rice infection. Our study provides evidence of a direct link between MoSnt2 and MoTor signaling and defines a novel epigenetic mechanism by which MoSNT2 regulates infection-associated autophagy and plant infection by the rice blast fungus. Abbreviations: M. oryzae: Magnaporthe oryzae; S. cerevisiae: Saccharomyces cerevisiae; F. oxysporum: Fusarium oxysporum; U. maydis: Ustilago maydis ; Compl.: complemented strains of Δ Mosnt2 expressing MoSNT2-GFP ; ATG: autophagy-related; HDAC: histone deacetylase complex; Tor: target of rapamycin kinase; MTOR: mechanistic target of rapamycin kinase in mammals; MoSnt2: DNA binding SaNT domain protein in M. oryzae ; MoTor: target of rapamycin kinase in M. oryzae ; MoAtg8: autophagy-related protein 8 in M. oryzae ; MoHos2: hda one similar protein in M. oryzae ; MoeIf4G: eukaryotic translation initiation factor 4 G in M. oryzae ; MoRs2: ribosomal protein S2 in M. oryzae ; MoRs3: ribosomal protein S3 in M. oryzae ; MoIcl1: isocitrate lyase in M. oryzae ; MoSet1: histone H3K4 methyltransferase in M. oryzae ; Asd4: ascus development 4; Abl1: AMP-activated protein kinase β subunit-like protein; Tig1: TBL1-like gene required for invasive growth; Rpd3: reduced potassium dependency; KAT8: lysine (K) acetyltransferase 8; PHD: plant homeodomain; ELM2: Egl-27 and MTA1 homology 2; GFP: green fluorescent protein; YFP: yellow fluorescent protein; YFP CTF : C-terminal fragment of YFP; YFP NTF : N-terminal fragment of YFP; GST: glutathione S -transferase; bp: base pairs; DEGs: differentially expressed genes; CM: complete medium; MM-N: minimum medium minus nitrogen; CFW: calcofluor white; CR: congo red; DAPI: 4ʹ, 6-diamidino-2-phenylindole; BiFC: bimolecular fluorescence complementation; RT: reverse transcription; PCR: polymerase chain reaction; qPCR: quantitative polymerase chain reaction; RNAi: RNA interference; ChIP: chromatin immunoprecipitation